ANALISIS FAKTOR – FAKTOR YANG BERPENGARUH TERHADAP KEPUTUSAN PEMBELIAN BERAS SEHAT DI KECAMATAN BELITANG - aisyah aisyah (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2022)
Healthy agriculture is to provide products especially food that is save, healthy for the consumer and does not damage the environment. The world’s agricultural product market healthy increase of 20% per year, therefore the development of healthy agricultural cultivation need to be prioritized on high-value crops to meet the needs of the domestic market and export. Rice is the most everyday food for most people of Indonesia, and rice is the staple food that can not be replaced by other carbohydrate soerces. Rice (rice) is 60% to 70% of the food we eat every day for most Indonesian people. So it is clear that as a staple food daily is most influential to our health. The objectives of this study were : 1) To determine what factor influence the buyers decision to comsume healthy rice. 2) To determine how much influence the healthy rice products to the purchasing decision in district Belitang healthy rice. The result show that there are factors that influence purchasing decisions helthy rice are : price, quality, nutrient content. But three variables are described together do not have a significant influence, while parsial three variables, namely the price, quality and nutrient content have a significant influence on purchasing decision in District Belitang healthy rice.keywords : Healthy rice, purchasing decision, domestic market and export.